توظيف السياق القرآني لتحديد دلالة المشترك اللفظي - AL-KIKI, ABBAS ABDUL QADIR HUSSEIN (Journal of Duhok University, 2020)
This research deals with the use of the context determine the meaning of the common word in every place without leaving behind any ampiguity in its meaning . This research is based on some of the Quraanic verses used in of these words . He showed hwo the Quran uses the context in both ways to guide the meaning of the common verbal and define its meaning , And that this is a facet of the faces of the Quran , And this research included the introducetion to ensure three things first : the conceptof context and language and terminology , second : the context of the importance of context in the statement of the meaning of the common verbal . The research then focused on main focus of this study , namely the use context todetermine the meaning of the common verbal , relying on the selection of some common words that were mentioned in the Quran to make it a materiel for the lesson , was the approach of research is the selection of some of the Quran that is suitable to be a witness to the suitable of the research , and then the research included a brief conclusion summarizing the most important results which the study found